Implementation of Islamic Spiritual (Rohis) Extracurricular Activities in Cultivating Students' Religious Character: A Qualitative Case Study at an Indonesian Public Senior High School - Asriyani; Wiwin Narti; Siti Khamim (CV Putra Publisher, 2024)
Religious character formation has become a strategic agenda within Indonesia's national education system, yet the limited weekly allocation of Islamic Religious Education at the senior secondary level constrains the effective internalization of religious values during adolescence. Although Islamic spiritual extracurricular activities (Rohis) are widely adopted as a pedagogical complement, prior studies remain predominantly descriptive and rarely integrate the implementation process, contextual enablers and barriers, and observable behavioral outcomes within a single analytical framework, particularly in non-metropolitan public schools. This study examines how the Rohis program is implemented and how it shapes students' religious character at SMA Negeri 7 Bungo, Jambi Province, Indonesia. A qualitative case study design was employed across one academic semester. Data were generated through participant observation of twelve program sessions, semi-structured in-depth interviews with eight purposively selected informants (vice principal of student affairs, Islamic Religious Education teacher, Rohis advisor, Rohis chairperson, and four active members), and the analysis of program documents and field notes. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while trustworthiness was secured through source and method triangulation, prolonged engagement, and member checking. Findings indicate that Rohis is operationalized through four structured programs weekly Tahsin (Yasinan), monthly Muhadarah and Mentoring, and annual commemorations of Islamic holy days (PHBI) facilitated by adequate facilities, institutional support, and advisor competence, but constrained by irregular attendance and uneven teacher supervision. Observable outcomes include consistency in worship and Quranic recitation, the emergence of leadership, responsibility, honesty, discipline, and humility. The study concludes that programmatically structured religious extracurricular activities, embedded in a supportive school ecosystem, function as a strategic vehicle for internalizing religious character at the senior secondary level.